Pterocarpus mildbraedii leaf extract ebbs propanil-induced oxidative and apoptotic damage in the liver of rats. (4th July 2022) - Otuechere, Chiagoziem A.; Farombi, Ebenezer O.
Abstract: Phytochemicals derived from plant sources are well recognized as sources of pharmacologically potent drugs in the treatment of several oxidative stress-related ailments. Dichloromethane/methanol (1:1) leaf extract of Pterocarpus mildbraedii was evaluated for its possible protection against oxidative stress and apoptosis in the liver of male Wistar rats exposed to propanil (PRP). In the experimental design, olive oil served as the vehicle, and rats were grouped into control (2 mL/kg olive oil), PRP (200 mg/kg/day), Pterocarpus mildbraedii extract (200 mg/kg/day), and Pterocarpus mildbraedii extract (200 mg/kg/day)+PRP (200 mg/kg/day), and treated daily, p.o., for seven days. Oxidative stress parameters, B-cell lymphoma 2 (Bcl-2), Bcl 2-associated X protein (Bax), p53, caspases (9/3), and terminal transferase dUTP nick end labeling (TUNEL) assays were observed in all groups. Propanil significantly elevated superoxide dismutase and lipid peroxidation levels, while concomitantly depleting GSH and p53 levels. Further, PRP enhanced the expressions of caspase-9, caspase-3, Bax, and TUNEL-positive cells in the liver of rats. However, these observed alterations were reversed following treatment with Pterocarpus mildbraedii extract. Our studies suggest that Pterocarpus mildbraedii extract protected against PRP toxicity by reducing oxidative stress and attenuating critical endpoints in the intrinsic apoptotic pathway.